An Evaluasi Pelaksanaan Workshop Daring Penerapan Ilmu Biologi di SMA Plus Al Wahid Tasikmalaya - Nisa Rachmania Mubarik; Mira Dewi; Jepri Agung Priyanto (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
The workshop on the application of Biology online (on a network) using the internet during the Covid-19 pandemic has been held at SMA Plus Al Wahid, Tasikmalaya Regency. This activity is in the context of a community service program entitled IPB lecturers to serve. The objectives of this activity are: 1) To describe the implementation of an online explanation workshop program for high school level Biology learning, especially those related to viruses and body immunity; 2) Explaining the level of understanding of the workshop participants before and after the presentation of the material; and 3) Explaining the results of the evaluation of participants' satisfaction with the delivery of workshop materials. The workshop was held on September 4, 2020 online using the Zoom application platform. The number of participants who took part in the workshop was 43 people, consisting of students in grades X, XI, and XII in the natural sciences, teachers, and the general public (non-teacher high school employees) from SMA Plus Al Wahid. Only 16 student participants who filled out the pre-test and post-test were used to evaluate this activity. Evaluation of the results of the pre-test and post-test using a one-group pre-test-post-test design using the N gain method or normalized gain analysis. The results of the workshop showed an increase in participants' understanding of the material on the application of Biology by 30.6% and participants showed a satisfaction level of 76.25%.